Legal Policy Recommendations for Terminating MBG in Indonesia - Ade Riusma Ariyana (International Journal of Law Society Services, 2025)
The Free Nutritious Meals (MBG) program is a populist policy designed to address stunting and improve the quality of human resources in Indonesia. However, from a legal-political perspective, the implementation of this policy faces fundamental challenges related to fiscal space, bureaucratic effectiveness, and potential regulatory overlap. This study aims to analyze the urgency of recommending termination or fundamental transformation of the MBG program through an analysis of state financial law and the principle of legal expediency. The research method used is normative juridical with a statutory and conceptual approach. The results of the study indicate that reliance on new debt financing for consumption programs risks violating the prudence principle in the State Finance Law. Furthermore, the establishment of the National Nutrition Agency triggers institutional redundancy that has the potential to lead to maladministration. This study recommends a policy reorientation toward a conditional cash transfer scheme and strengthening basic sanitation infrastructure that is more legally and economically sustainable.